2020
DOI: 10.34172/hpr.2020.06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on Risk Factors and Clinical Manifestations of Acute Coronary Syndrome: Observations From the Coronary Care Unit of Sulaimani, Iraq

Abstract: Background: ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI ) are common types of acute coronary syndrome which are associated with the risk factors of age, obesity, hypertension, and diabetes. Objective: The present study aimed to examine the effects of age on the risk factors and clinical symptoms of acute coronary syndrome. Methods: A cross-section prospective study was conducted on 125 patients with acute coronary syndrome chosen by non-proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Risk factorMany risk factors contribute to the development of myocardial infarction, including age, gender, family history, smoking, high blood pressure, diabetes, obesity, physical inactivity, and high cholesterol levels(1)(2)(3)(4)(5)(6). Studies have shown that the prevalence of these risk factors differs between patients over 40 and under 40(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Risk factorMany risk factors contribute to the development of myocardial infarction, including age, gender, family history, smoking, high blood pressure, diabetes, obesity, physical inactivity, and high cholesterol levels(1)(2)(3)(4)(5)(6). Studies have shown that the prevalence of these risk factors differs between patients over 40 and under 40(3)(4)(5)(6).…”
mentioning
confidence: 99%